Environmental Processes - Environmental Processes (Springer Nature, 2026)
Environmental Processes covers: processes related to the interactions of the water, air-atmosphere, and soil-sediment environments with the humans and the biosphere; environmental flow processes, hydrodynamics and hydrology; pollutant physical, chemical and biological processes, including pollutant sources and origin, fate, dispersion and degradation, transport, deposition and accumulation, and impacts on human health and environmental quality; interaction processes between the social, cultural, economic and natural environments; evaluation of currently applied and new proposed technologies for pollutant treatment and the protection of the environment; testing of currently used and new proposed monitoring, instrumentation and analysis techniques related to the environmental processes; educational, regulatory, and research needs on environmental processes and protection.
FI 0.41
Q3
Keywords: Earth; Space & Environmental Sciences; Environmental Geoscience; Acuerdos transformativos; Transformative agreements; Procesos ambientales; Hidrología; Interacción agua-atmósfera-suelo; ransporte de contaminantes; Hidrodinámica; Procesos biogeoquímicos